Effects of thinning on the structure of soil microbial communities in a subtropical secondary evergreen broad-leaved forest - Liangjin Yao; Jiejie Jiao; Chuping Wu; Bo Jiang; Lili Fan (Frontiers in Plant Science)
IntroductionThinning is a common practice to enhance tree growth, but its effect on rhizosphere soil microorganisms in subtropical secondary evergreen broadleaved forests remains unclear.MethodsThis study used 16S rDNA amplicon sequencing to explore soil microflora of five shrubs and five tree species.ResultsThe results showed that thinning altered nutrient distribution and pH in rhizosphere soil, impacting microbial richness, which varied by tree species. The dominant bacterial phyla were Acidobacteria, Proteobacteria, Actinobacteria, and Firmicutes. Although the dominant microbial species remained largely unchanged, thinning increased the relative abundance of Firmicutes. Thinning intensity between 10-15% significantly altered the structure of soil microbial communities, demonstrating species-specific responses.DiscussionThese changes in microbial structure may influence tree growth. This study proposed the potential effects of thinning on rhizosphere soil microorganisms and suggests future research to investigate the specific microbial mechanisms affected by thinning.